Mexico's Currency Risk Premia in 1992-1994 : A Closer Look At the Interest Rate Differentials - Werner, Alejandro (IMF Working Papers; Working Paper, 1996)
This paper studies the behavior of interest rate differentials in Mexico during the 1992-94 period. It shows that the currency risk premia is positively related to the share of peso denominated debt in total debt and that the magnitude of this effect is considerable. For every 1 percentage point increase in the ratio of peso denominated debt in total debt, the interest rate differential increases between 20 and 30 basis points. In light of this result, and to get a better measure of the expectation of a devaluation during the period, the observed interest rate differential is adjusted for the change in the composition of public debt. In contrast to the behavior of the interest rate differential, the adjusted measure remained at extremely high levels throughout 1994, signalling a low level of confidence in the announced currency band.